-6(x-2)-2x=4-8(x+3)

Simple and best practice solution for -6(x-2)-2x=4-8(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x-2)-2x=4-8(x+3) equation:


Simplifying
-6(x + -2) + -2x = 4 + -8(x + 3)

Reorder the terms:
-6(-2 + x) + -2x = 4 + -8(x + 3)
(-2 * -6 + x * -6) + -2x = 4 + -8(x + 3)
(12 + -6x) + -2x = 4 + -8(x + 3)

Combine like terms: -6x + -2x = -8x
12 + -8x = 4 + -8(x + 3)

Reorder the terms:
12 + -8x = 4 + -8(3 + x)
12 + -8x = 4 + (3 * -8 + x * -8)
12 + -8x = 4 + (-24 + -8x)

Combine like terms: 4 + -24 = -20
12 + -8x = -20 + -8x

Add '8x' to each side of the equation.
12 + -8x + 8x = -20 + -8x + 8x

Combine like terms: -8x + 8x = 0
12 + 0 = -20 + -8x + 8x
12 = -20 + -8x + 8x

Combine like terms: -8x + 8x = 0
12 = -20 + 0
12 = -20

Solving
12 = -20

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4x^2-(-32)=-28 | | 5(z+2)=3(z+1)-1 | | 4x^2-32=-28 | | x^3+3x^2+6x+1= | | (10y-6)/(9y^2-15y) | | (9x-8)/(-6x-7) | | Y-5=x^2-6x+2 | | X^2-4x-1=-15 | | 2x^2-13=5x^2+12 | | 4x=15-(-15) | | x^3+3x^2-70x-144=0 | | 2x+50=120 | | 22=13-y | | v^2-5v-126=0 | | 2(3x+4)=19x | | 6x-2=27x+10 | | -7=-28-7 | | 12-48=3(x-4)-6 | | 3(x-4)-6=12-48 | | 2y-1/3=4y | | 12-6k=36 | | -16=0.1x-0.5x | | x^2+100=125 | | X=arcsiney | | 2x+5x=88 | | m+2+m-5=15 | | lg(x-1)=0 | | 4x^3-4x^2+x=o | | 22-9x=-5(6x+3)-5(-4-4x) | | 13+X=37 | | 3x+5y=8fory | | 5[4-(-3)(2)]= |

Equations solver categories